THE SKILL OF IMPROVISATION AS THE BASIS OF A LIVE ACTING PRESENCE - Котик, Ірина (SWorldJournal, 2025)
The relevance of the study is due to the growing role of improvisational skills as a key factor in ensuring a live actor’s presence in the conditions of modernization of modern theater pedagogy. The study was conducted with the aim of comprehensively subs